Isolation and chromosomal location of putative vitelline membrane genes in Drosophila melanogaster. - Mindrinos, M N (1985)
cDNA clones for two Drosophila vitelline membrane genes have been identified on the basis of: (i) stage and tissue specificity of transcription and (ii) size and amino acid content of the translation product. Cross-hybridization data suggest that DmcMM99 and DmcMM115 are members of a multi-gene family which includes at least three members, all of which reside on the left arm of the second chromosome. DmcMM99 and DmcMM115 originate from polytene band positions 34C and 26A, respectively. A third, cross-hybridizing gene resides at position 32EF. Southern analysis of a genomic clone, lambda LS1, homologous to DmcMM115, indicates that two vitelline membrane genes may be clustered at the 26A site.